Предмет: Математика,
автор: АДИНКА2005
а-(а-(а-в)-(в-а)-в)=?
Ответы
Автор ответа:
1
Раскрываем скобки :)
а-(а-(а-b)-(b-a)-b)=
a-a+(-a+b)+(-b+a)+b=
a-a-a+b-b+a+b=b
Ответ: b
__________
С уважением, S̰ḛc̰ṵr̰ḛ
а-(а-(а-b)-(b-a)-b)=
a-a+(-a+b)+(-b+a)+b=
a-a-a+b-b+a+b=b
Ответ: b
__________
С уважением, S̰ḛc̰ṵr̰ḛ
АДИНКА2005:
cпс
Похожие вопросы
Предмет: Математика,
автор: Dashyta0Shadow
Предмет: Русский язык,
автор: mskdjsj
Предмет: Математика,
автор: hobotovaulia96
Предмет: Литература,
автор: СофьяРыженкова
Предмет: Геометрия,
автор: lina059